Disentangling Associations Among Maternal Lifetime and Prenatal Stress, Psychological Functioning During Pregnancy, Maternal Race/Ethnicity, and Infant Negative Affectivity at Age 6 Months: A Mixtures Approach - Campbell, Rebecca K. (Health Equity, 2020)
Purpose: Maternal stress and psychological dysfunction in pregnancy are independently linked with fetal neurodevelopment. Stress encompasses environmental stressors and psychological and physiological responses. Stressors and psychopathology co-occur with patterns differing by race/ethnicity. We aimed to extend environmental mixtures methodology to elucidate prenatal stress associations with infant negative affectivity (NA) in a racially/ethnically mixed cohort. Methods: Participants were mother/infant dyads (n=445) in a prospective pregnancy cohort study in two urban US settings in 2011–2018. During pregnancy, women completed the Life Stressor Checklist-Revised, Crisis in Family Systems-Revised, Edinburgh Postnatal Depression Scale, and post-traumatic stress disorder (PTSD) Checklist-Civilian version; the Infant Behavior Questionnaire-Revised assessed NA in 6-month olds. Using weighted quantile sum (WQS) regression, we developed a weighted maternal stress index encompassing lifetime and current life events and symptoms of depression and PTSD. Stress-by-race/ethnicity interactions allowed differential contributions of individual stress domains by maternal race/ethnicity. Results: Mothers were majority black (44%) or Hispanic (37%). Stress questionnaire and infant NA scores were similar by race/ethnicity. The WQS prenatal stress score was positively associated with infant NA (β: 0.40 [95% confidence interval 0.16–0.64]). PTSD was the strongest contributor to the WQS score in Hispanic women (59%), whereas in black women, lifetime stress and depressive symptoms accounted for 38% and 35%, respectively, of the association with NA. Conclusions: Extending environmental mixtures methodology to stress research may disentangle complex associations among lifetime and current stressful life events and psychological symptomatology and their contributions to early childhood neurobehavioral outcomes. Consideration of effect modification by race/ethnicity may inform understanding of differing vulnerability across racial/ethnic groups.